Fractional high-order harmonic combs and energy tuning by attosecond-precision split-spectrum pulse control - Raith, Philipp Nils; Ott, Christian; Anderson, Christopher P.; Kaldun, Andreas; Meyer, Kristina; Laux, Martin; Pfeifer, Thomas (Applied physics letters, 2012)
We experimentally control high-order harmonic generation by applying a versatile few-cycle pulse-shape control method: splitting up a single broadband continuous laser spectrum into two sections and applying sub-femtosecond relative time delays. For certain time delays, fractional high-harmonic combs (noninteger harmonics) are generated which we find to result from the controlled interference of two attosecond pulse trains. We also observe time-delay-dependent energy-tunability of the high-order harmonics for an asymmetrically split spectrum consisting of a strong and a weak component. The tuning mechanism is quantitatively understood by the controlled modulation of the instantaneous driver frequency at the peak of the shaped laser pulse.
Gesehen am 27.11.2018